Sistema especialista para manutenção de subestação HVDC utilizando a metodologia de apoio a tomada de decisão multicritério - Andrade, Camila Maciel (2023)
Brazilian HVDC (High Voltage Direct Current) transmission systems are relevant to the electricity sector due to their ability to transmit a bulk of energy over large distances. Performing equipment maintenance is the most effective way to increase the reliability of HVDCs that are critical to maintaining systemic stability. Annually, in the preferential period between September and November, each one of the HVDCs in Brazil has 80 hours to perform scheduled maintenance with shutdown of equipment that is part of the converter transmission function without payment of a variable portion. HVDC substations are characterized by a amount greater than 1000 equipments in your configuration, that is, a high value in relation to the majority of substations in alternating current because of this, carrying out an optimized planning so that during the 80 hours of shutdown the greatest possible amount of corrective and preventive maintenance is performed becomes a problem. In this way, the present work proposes the development of an Expert System for HVDC substation maintenance using the methodology of the multi-criteria decision making methodology with the application of the Analytic Hierarchy Process (AHP) method.The following criteria were considered for the analysis: reliability, equipment cost, variable portion, equipment replacement time, and historical alarms and events. As a result, a simplified demonstration of the equipment hierarchy of an HVDC substation was obtained, which must be prioritized for maintenance in the annual shutdown, and thus help in the planning of activities.